Financial Feasibility Analysis of Shrimp Vannamei (Litopenaeus vannamei) Culture in Intensive Aquaculture System with Low Salinity - Heri Ariadi; Mohamad Fadjar; Mohammad Mahmudi (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2019)
The prevalence of disease spread caused by improper cultivation systems causes a decrease in the productivity level of vannamei shrimp ponds. A low salinity cultivation system is one of the cultivation innovations that can be developed to reduce the spread of disease. The purpose of this study was to describe water quality status on aquatic shrimp culture and business financial feasibility in the intensive vannamei shrimp (Litopenaeus vannamei) culture with low salinity levels. The research method used was quantitative descriptive with a purposive sampling technique of data collection. The result of the research is the Water Quality Index analysis value of 110 which means it is very suitable to be used as a cultivation medium. Profitability analysis produces a profit value of Rp. 244,456,603, R/C Ratio 1.35, BEP Unit 3,797, BEP Sales Rp. 188,745,587, and Profitability 35%. Meanwhile, the financial analysis of the business found that the NPV value was Rp. 19,627,985,863, the Profitability Index was 25.43%, the IRR was 27.55%, and the Payback Period was 5 years, which meant that this business was very feasible to be developed based on its financial feasibility status criteria. So that the overall, low salinity shrimp culture is very feasible to be applied when viewed from the ecological or economic advantage, and can be used as an alternative for vannamei shrimp aquaculture in areas that have the location of a pond far from the source of marine water.